Manifestações Fonoaudiológicas em um grupo de doentes de Hanseníase - Barbosa, Janayne Cunha (2007)
Introduction: Hansen s Disease, an infectious illness of compulsory notification is caused by Hansen s bacillus (Mycobacterium leprae), and may present multiple lesions on any body part, most frequently harming the face, ears, nose and the oral cavity. Aim: The aim of the present study is to evaluate, by means of the patients history and Speech Therapy evaluation, the auditory (auditory thresholds), vocal (vocal characteristics and maximum phonation times), and oral-facial functions (chewing, breathing, swallowing and speech) manifestations in Hansen s Disease patients of a public health center of the city of São Paulo/SP. Methods: The subjects of this study were 20 Hansen s Disease patients, between 18 and 45 years of age. Specific protocols were filled out for each patient. These protocols targeted the subjects auditory, vocal, and oral-facial functions history. Then, these aspects were evaluated through specific Speech Therapy evaluation methods. The results were described numerically and by percentages. Results: Considering the subjects who took part in this study (55% female and 45% mal), 45% had paucibacillary (PB) and 55% multibacillary (MB) Hansen s disease, and all were receiving treatment (MDT/monotherapy). Five subjects complained of auditory changes, three of vocal changes and two of altered oral-facial functions. Discussion:Case description may aid the speech therapist and other members of the multidisciplinary team to better understand the Disease, and its possible speech therapeutic manifestations; as well as to create various hypothesis and to clinically evaluate and design adequate treatment for these patients. Conclusion: The speech therapeutic manifestations observed were few, and it was not possible to establish that the occurrences of the observed alterations were related to Hansen s Disease. This fact may be justified by the patients adequate usage of medication, as well as by the short time-span between diagnosis and the beginning of treatment, and to the age-span considered in this research (18 to 45 years)